Analysis of the Effect of Education, Population, Employment, Minimum Wages on Poverty in Riau Province 2017-2021: Analisis Pengaruh Pendidikan, Jumlah Penduduk, Tenaga Kerja, Upah Minimum, terhadap Kemiskinan Provinsi Riau Tahun 2017- 2021 - Pertiwi, Mayang Umi; Setyowati, Eni (Procedia of Social Sciences and Humanities, 2022)
This study entitled the effect of education, population, employment and district minimum wages on poverty in Riau Province in 2017-2021. This study aims to determine the magnitude of the effect of the dependent variable on the independent variable. The data analysis method used is panel data using Eviews 8. From the data it can be concluded that the variables of education, population, employment, district minimum wages affect the poverty variable. Partially, the population variable has a positive effect on the poverty variable, and the district minimum wage has a negative effect on poverty.